2021
DOI: 10.3390/f12010087
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Thickness on the Tensile Strength of Finnish Birch Veneers under Varying Load Angles

Abstract: The development of high-performance, veneer-based wood composites is a topic of increasing importance due to the high design flexibility and the comparable mechanical performance to solid wood. Part of this improved mechanical performance can be contributed to the size effect present in wood. Based on previous findings in the literature, this size effect can be either strengthening or weakening. The presented study investigates the influence of thickness and load angle on the tensile strength and tensile stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…A strong dispersion was observed on the longitudinal Young's modulus [0°]1 specimens. It should be noted, however, that the dispersion observed was of the same order of magnitude as that observed by other authors on tensile tests on 1-ply 1 mm veneers (Pramreiter et al 2021). In addition, the average stiffness value obtained in these tests was of the order of magnitude of the values found in the literature.…”
Section: Longitudinal Young's Modulus Of [0°]1 Specimenssupporting
confidence: 82%
See 2 more Smart Citations
“…A strong dispersion was observed on the longitudinal Young's modulus [0°]1 specimens. It should be noted, however, that the dispersion observed was of the same order of magnitude as that observed by other authors on tensile tests on 1-ply 1 mm veneers (Pramreiter et al 2021). In addition, the average stiffness value obtained in these tests was of the order of magnitude of the values found in the literature.…”
Section: Longitudinal Young's Modulus Of [0°]1 Specimenssupporting
confidence: 82%
“…The standards for tensile tests on wood-based panels, and therefore on plywood and LVL, recommend the design of 'bone-shaped' specimens to reduce the transverse cross-section of the specimen and avoid breakage of the specimen in the jaw area (ASTM D1037-99 and NF EN 789). Given the small thickness of wood veneers and their fragility, their machining to obtain a bone shape causes the specimens to break (Pramreiter et al 2021). The choice to characterize specimens with rectangular geometry and to add beads is, therefore, often made to avoid breaking of the jaws during the tensile test (Shupe et al 1998;Wu et al 2005;Jeong et al 2010;Pramreiter et al 2021;Lechner et al 2021).…”
Section: Materials and Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pramreiter et al [22] presented the importance of the development of veneer-based wood composites due to the high flexibility of design and mechanical strength compared to solid wood. The study showed the influence of veneer thickness on tensile strength compared to solid wood.…”
Section: Veneers]mentioning
confidence: 99%
“…Due to the occurrence of slicing checks being mainly in the wood radial direction and surface checking occurring when the material is under surface tension loading, it is assumed that tensile strength perpendicular to the grain is a critical parameter that could describe veneer or sliced lamellae mechanical performance. Regarding this aspect, a relevant study represents the investigation of the mechanical properties of plainand lengthwise-sliced beech lamellae [6] and birch rotary-cut veneers [23]. Hence, these studies evaluated low slicing thicknesses, i.e., 0.5-1.5 mm.…”
Section: Introductionmentioning
confidence: 99%